30 Birth and Rebirth - Parental Experiences of Their Newborn Infants Treated with Hypothermia Following Perinatal Asphyxia. (October 2012) - Nassef, S Kokkonen; Blennow, M; Jirwe, M
Abstract : The normal caring and nursing of newborn infants is to keep them warm and close to their parents. Fullterm newborn infants suffering from perinatal asphyxia are treated with induced hypothermia treatment (IHT) for three days at the Neonatal Intensive Care Unit (NICU) in order to prevent or decrease brain damages. The design of the study was a descriptive qualitative study. The aim was to describe and understand experiences of parents whose newborn infants were treated with IHT following perinatal asphyxia. A total of ten parents participated in the study, seven mothers and three fathers. Open-ended recorded interviews were conducted 4–12 months after the birth of their infants. Inductive content analysis was used as method of analysis. Four main themes emerged from the data: emotional landscapes, adaptation to a new situation (with subthemes: creating control, external and internal support in a difficult situation, normalizing the abnormal and reconciliation to uncertainty), moments of rebirth and transformation of attitudes towards life and the existence.